2019
DOI: 10.3390/ijms20092228
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Bioinformatics Analysis of UBE2C in Cancers

Abstract: Ubiquitination is one of the main post-translational modification of proteins. It plays key roles in a broad range of cellular functions, including protein degradation, protein interactions, and subcellular location. In the ubiquitination system, different proteins are involved and their dysregulation can lead to various human diseases, including cancers. By using data available from the Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) databases, we here show that the ubiquitin conjugating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 57 publications
8
94
0
Order By: Relevance
“…malignant tumors, and this upregulation is significantly associated with lymph node metastasis and tumor stage. In addition, high expression of UBE2C is also closely associated with breast cancer, colon cancer and other malignant tumors (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…malignant tumors, and this upregulation is significantly associated with lymph node metastasis and tumor stage. In addition, high expression of UBE2C is also closely associated with breast cancer, colon cancer and other malignant tumors (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 46 ), revealed that UBE2C is highly expressed in gastric cancer, which could lead to the occurrence and development of malignant tumors, and this upregulation is significantly associated with lymph node metastasis and tumor stage. In addition, high expression of UBE2C is also closely associated with breast cancer, colon cancer and other malignant tumors ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…UBE2C (Ubiquitin-conjugating enzyme E2C) protein is involved in the ubiquitination process that modifies the abnormal or short-lived proteins with ubiquitin and target toward degradation (van Wijk et al, 2010). A good number of studies showed high expression of UBE2C is associated with aggressive progression and poor outcomes of several cancer (Dastsooz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Oncomine (https://www.oncomine.org) (16) and TCGA (https://tcga-data. nci.nih.gov/tcga/) databases (17,18), and GEPIA (http://gepia. cancer-pku.cn) (18,19), were used to estimate the expression of MELK in LUAD and adjacent normal tissues (16)(17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…nci.nih.gov/tcga/) databases (17,18), and GEPIA (http://gepia. cancer-pku.cn) (18,19), were used to estimate the expression of MELK in LUAD and adjacent normal tissues (16)(17)(18)(19). The search parameters in Oncomine were as follows: Analysis type, cancer vs. normal; data source, public; cancer type, selected specific cancer type; sample type, clinical specimen and; data type, mRNA.…”
Section: Methodsmentioning
confidence: 99%